DAMPAK LABELLING KEPADA MANTAN WARGA BINAAN NARKOTIKA DI KECAMATAN TUALANG KABUPATEN SIAK - Farhan,; Fakhri Usmita, (Sisi Lain Realita, 2024)
The label of former inmate attached to someone will have an impact on their social life. The effects of labeling can be a barrier to the realization of training goals and social reintegration between inmates and society, thus affecting the lives of former inmates. This research aims to describe the impact of labeling on former narcotics inmates. To obtain strong and in-depth evidence and analysis, this research uses qualitative methods. This qualitative method makes it possible to explain in detail the problems that are the focus of the research better. The informants in this research involved the Head of the Class II B Siak Detention Center, the Secretary of the Tualang Village Head, community and community leaders. while the key informants in this research were former inmates themselves. The results of the interviews conducted by the author are that there are people who label and discriminate against former inmates, but there are also those who choose to accept and give former inmates the opportunity to change. The labeling and discrimination received by former inmates has a negative impact on the former inmates themselves, including hampering the rehabilitation and reintegration process of former inmates, the labeling and discrimination received can also affect the psychology of former inmates.